2021
DOI: 10.1108/lht-08-2021-0274
|View full text |Cite
|
Sign up to set email alerts
|

What drives continuance intention to use a food-ordering chatbot? An examination of trust and satisfaction

Abstract: PurposeArtificial intelligence (AI) customer service chatbots are a new application service, and little is known about this type of service. This study applies service quality, trust and satisfaction to predict users' continuance intention to use a food-ordering chatbot.Design/methodology/approachThe proposed model and hypotheses are tested using online questionnaire responses to collect users' perceptions of such services. One hundred and eleven responses of actual users were received.FindingsEmpirical result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 65 publications
2
19
0
Order By: Relevance
“…Their results revealed that e-service quality positively predicts e-trust in the digital economy, e-trust predicts e-loyalty and e-trust mediates the relationship between e-service quality and e-loyalty links. Readers may also be interested in reading further into e-trust issues on social media (Nabi et al ., 2023; Wang et al ., 2021; Wang and Tse, 2022; Ye and Ho, 2023; Yuan and Bi, 2023; Zhang et al ., 2023a, b, c), contact-tracing apps (Ho et al ., 2023a, b) and chatbots (Hsiao and Chen, 2022). Besides, readers may be interested in issues related to library promotion and marketing (Chan et al ., 2020; Cheng et al ., 2020; Fong et al ., 2020; Kwan et al ., 2023; Lam et al ., 2019, 2023; Liu et al ., 2023; Sahli et al ., 2023; Wójcik, 2022; Wu and Yang, 2022).…”
Section: Advances In Library Information Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results revealed that e-service quality positively predicts e-trust in the digital economy, e-trust predicts e-loyalty and e-trust mediates the relationship between e-service quality and e-loyalty links. Readers may also be interested in reading further into e-trust issues on social media (Nabi et al ., 2023; Wang et al ., 2021; Wang and Tse, 2022; Ye and Ho, 2023; Yuan and Bi, 2023; Zhang et al ., 2023a, b, c), contact-tracing apps (Ho et al ., 2023a, b) and chatbots (Hsiao and Chen, 2022). Besides, readers may be interested in issues related to library promotion and marketing (Chan et al ., 2020; Cheng et al ., 2020; Fong et al ., 2020; Kwan et al ., 2023; Lam et al ., 2019, 2023; Liu et al ., 2023; Sahli et al ., 2023; Wójcik, 2022; Wu and Yang, 2022).…”
Section: Advances In Library Information Managementmentioning
confidence: 99%
“…e-trust issues on social media (Nabi et al, 2023;Wang et al, 2021;Wang and Tse, 2022;Ye and Ho, 2023;Yuan and Bi, 2023;Zhang et al, 2023a, b, c), contact-tracing apps (Ho et al, 2023a, b) and chatbots (Hsiao and Chen, 2022). Besides, readers may be interested in issues related to library promotion and marketing (Chan et al, 2020;Cheng et al, 2020;Fong et al, 2020;Kwan et al, 2023;Lam et al, 2019Lam et al, , 2023Liu et al, 2023;Sahli et al, 2023;W ojcik, 2022;Wu and Yang, 2022).…”
mentioning
confidence: 99%
“…Anthropomorphism has a profound influence on users' interaction with AI technologies. It can foster positive attitudes, trust, and engagement among users, which in turn affects their purchase intention and overall satisfaction with the technology Lu et al, 2019;Stroessner & Benitez, 2019;Hsiao & Chen, 2021). This arises because people are naturally inclined to seek social connections and build relationships, even with AI systems (David-Ignatieff et al, 2023;Epley et al, 2007;Pizzi et al, 2023).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…They highlighted emerging research themes; collaborations such as authors, institutions, journals and co-citations such as documents, authors and journals. Readers may also be interested in Hsiao and Chen (2021) about the continuance intention to use a food-ordering chatbot. Notably, CiteSpace is a common tool used by Song et al (2020) for analyzing LIS research articles, Zhao et al (2021) for psychological processing of contextual cues, Liu and Li (2021) for land use and carbon emissions and Feng et al (2022) for cultural and creative design.…”
Section: Studies On Science Researchmentioning
confidence: 99%